Opportunities for Energy Demand and Carbon Emissions Reduction in the Chemicals Sector. (May 2017) - Griffin, Paul W.; Hammond, Geoffrey P.; Norman, Jonathan B.
Abstract: The opportunities and challenges to reducing industrial energy demand and carbon dioxide (CO2 ) emissions in the Chemicals sector are evaluated with a focus is on the situation in the United Kingdom (UK), although the lessons learned are applicable across much of the industrialised world. This sector can be characterised as being quite heterogeneous, and as sitting on the boundary between energy-intensive (EI) and non-energy-intensive (NEI) industrial sectors. Currently-available technologies will lead to further, short-term energy and CO2 emissions savings in chemicals processing, but the prospects for the commercial exploitation of innovative technologies by mid-21st century are far more speculative. The chemicals sector has long been the largest owner of generating plant in UK industry. Most generation is from CHP plant with significant amounts of excess electricity exported to the grid or other industrial sectors. Special care was taken not to 'double count' auto-generation and grid decarbonisation; so that the relative contributions to decarbonisations of each was accounted for separately. There are a number of non-technological barriers to the take-up of such technologies going forward. Consequently, the transition to a low carbon future in UK industry by 2050 will exhibit rather large uncertainties. The attainment of significant falls in carbon emissions over this period will depends critically on the adoption of a small number of key technologies [e.g., carbon capture and storage (CCS), energy efficiency techniques, and bioenergy], alongside a decarbonisation of the electricity supply.